Two Dimensional Descriptors Based on Degree, Neighborhood Degree, and Reverse Degree for HEX (Hexagonal) Lattice - Asima Razzaque; Saima Noor; Salma Kanwal; Saadia Saeed (Journal of Mathematics)
Crystal structures are of great scrutiny due to the elegant and well-ordered symmetry that influences a significant role in determining numerous physical properties. Our aim is to perceive the role of topological descriptors in the field of crystallography using chemical graph theory to examine symmetrical crystal structure HEX. Simple hexagonal (HEX) is a crystal structure formed by arranging the same layer of atoms in a hexagon with one additional atom at the center. Chemical graph theory allows us to study a variety of molecular structures via graphical representation where each atom is denoted as a vertex and the bond form between them is defined as edge. In this research work, we compute the general Randic^ index, atom bond connectivity index, geometric arithmetic index, first and second Zagreb indices. Furthermore, we will compute their neighborhood and reverse degree-based versions and visualize which descriptor stands high in accordance with its numerical value.